2017
DOI: 10.1136/injuryprev-2016-042296
|View full text |Cite
|
Sign up to set email alerts
|

Use of life jackets and other types of flotation for in-water recreation in designated swim areas in Washington State

Abstract: Flotation devices were frequently used for recreational wading and swimming in open water by all age groups. Life jacket use was limited to children. Promoting use of flotation devices with safety standards that provide protection as well as fun could potentially decrease open water drowning rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…80 Another observational study of swimmers and waders in designated swim areas revealed that life jacket and other flotation device use decreased with increasing age, with 50% of children younger than 6 years using a life jacket compared with 3% of adults. 81…”
Section: Boatersmentioning
confidence: 99%
“…80 Another observational study of swimmers and waders in designated swim areas revealed that life jacket and other flotation device use decreased with increasing age, with 50% of children younger than 6 years using a life jacket compared with 3% of adults. 81…”
Section: Boatersmentioning
confidence: 99%
“…However, introducing and requiring their use among young children probably explains their increased, though not mandated use among young adolescents [ 23 ]. Life jacket use for swimming and playing in the water has been successful among young children; 50% of observed young children wore them in open water [ 25 , 26 ]. Barriers to life jacket use include knowing how to choose and fit them properly and cultural changes, and the perception that they denote an inexperienced boater or weak swimmer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some emergency circumstances, where immersion is sudden and unintentional, reliance on unsupported flotation (of self or others) may be the only means of maintaining the airway and providing time to facilitate rescue or escape. In other instances, where water immersion is intended, the use of external buoyancy aids (such as PFDs) or other improvised sources of buoyancy (such as plastic containers, wetsuits, surfboards) will help reduce the threat of drowning (Cummings, Mueller, & Quan, 2011;Quan, Mangione, Bennett, & Chow, 2017;Quistberg, Quan, Ebel, Bennett, & Mueller, 2014). Competency in, and perceptions of, supported flotation via PFD use are beyond the scope of this first phase of the Can you Float?…”
Section: Introductionmentioning
confidence: 99%